Do Individual and Situational Factors Explain the Link Between Predrinking and Heavier Alcohol Consumption? An Event-Level Study of Types of Beverage Consumed and Social Context - Labhart, F.; Wells, S.; Graham, Kathryn; Kuntsche, E. (Medical Council on Alcohol and Oxford University Press, 2014)
Aim: Predrinking (drinking in private settings before going to licensed premises) has been shown to be positively associated with amount of alcohol consumed. The present study assesses whether this association is explained by general drinking patterns or situational factors, including drinking duration, beverage type and drinking companions. Methods: In a sample of 183 young adults from French-speaking Switzerland, data on alcohol consumption, whereabouts and drinking companions were collected using questionnaires sent to participants’ cell phones at five time points from 5 p.m. to midnight every Thursday, Friday and Saturday over five consecutive weeks. Means and proportion tests and multilevel models were conducted based on 6650 assessments recorded on 1441 evenings. Results: Over the study period, predrinkers drank more frequently than did non-predrinkers and, among males, predrinkers drank more heavily. Predrinking was related to increased drinking duration and thus total consumption in the evenings. Larger groups of people were reported for predrinking compared with off-premise only drinking situations. Among women, the consumption of straight spirits (i.e. not mixed with soft drinks) while predrinking was associated with higher total evening alcohol consumption. Among men, drinking with exclusively male friends or female friends while predrinking was associated with higher consumption. Conclusion: Heavier drinking on predrinking evenings mainly results from longer drinking duration, with individual and situational factors playing a smaller role. Prevention efforts on reducing the time that young adults spend drinking and harm reduction measures such as restriction of access to on-premise establishments once intoxicated are recommended.